Ethnic In-and Out-Group Friendships Going Into Early Adolescence: Prevalence, Quality, Stability, and the Role of the Network Structure. (August 2023) - Oczlon, Sophie; Boda, Zsófia; Schwab, Susanne; Bardach, Lisa; Lehofer, Mike; Lüftenegger, Marko
The present study sought to investigate the friendship formation of ethnic in-and out-group friendships, as well as differences in stability and quality, while accounting for the network structure (such as the tendency to befriend friends of friends). We analyzed longitudinal data from 770 students from 42 Austrian primary school classes collected over the course of their last year of primary school. First, friendship prevalence, quality and stability were investigated using multiple regression quadratic assignment procedures. Then, friendship creation and stability were modeled over time using multilevel stochastic actor-oriented models. The results did not show significant differences between the creation of in-and out-group friendships; however, it was found that in-group friendships were more stable over time. The results further underscore the importance of considering network structure effects when analyzing intergroup friendship prevalence, creation, and stability.